Anthropometric Measurements and Lipid Profiles to Detect Early Lipodystrophy in Antiretroviral Therapy Experienced HIV-Infected Children in the Chapas-3 Trial. Issue 3 (April 2014) - Musiime, Victor; Cook, Adrian; Kayiwa, Joshua; Zangata, Dorothy; Nansubuga, Carol; Arach, Beatrice; Kenny, Julia; Wavamunno, Priscilla; Komunyena, Justine; Kabamba, Desiree; Asiimwe, Alice R; Mirembe, Grace; et al.
Background: Few studies have investigated objective markers of lipodystrophy in African children. We compared body circumferences, skin-fold thickness (SFT) and lipids in antiretroviral therapy (ART)-naive and stavudine (d4T)-exposed children with HIV-uninfected controls. Methods: In the CHAPAS-3 trial, HIV-infected children (ART-naive or on d4T for ≥2 years without clinical lipodystrophy) were randomized to d4T, abacavir or zidovudine with lamivudine (3TC) plus a non-nucleoside reverse transcriptase inhibitor. Mid-upper-arm circumference (MUAC) and calf circumference (CC), SFT (biceps, triceps, sub-scapular and supra-iliac) and fasting lipids (total cholesterol [TC], low-density lipoprotein [LDL], high-density lipoprotein [HDL] and triglycerides [TRIG]) were measured at randomization in all HIV-infected children, and in HIV-uninfected controls. Age- and sex-adjusted z-scores of MUAC, CC, SFT and the sum of SFT (SSF) using Dutch reference data were compared across groups using linear regression. Results: Of 496 children, 49% were male, 299 (median age 2.5 years [IQR 1.5–4.0]) were ART-naive, 109 (median age 6 years [IQR 5.5–7.0]) were ART-experienced and 88 (median age 2.2 years [IQR 1.5–3.0]) were control children. Overall, 100% and 95% of ART-experienced children had been on d4T plus 3TC and nevirapine, respectively, for a median 3.5 years (IQR 2.6–4.2). Mean (sd ) weight-for-age z-scores and MUAC z-scores were -1.51 (1.29) versus -0.90 (0.88) versus -0.33 (1.15) and -1.56 (1.25) versus -1.24 (0.97) versus -0.65 (1.06) in ART-naive versus -experienced versus controls, respectively (all P <0.02). The mean (sd ) of SSF was lower in the ART-experienced (-0.78 [1.28]) than in the ART-naive (-0.32 [1.09]; P <0.0001) children and controls (-0.29 [0.88]; P <0.002). ART-experienced children had higher mean fasting TC, LDL and HDL but lower TRIG compared to ART-naive children ( P -values <0.0001), and higher TC and HDL but lower TRIG compared to controls ( P -values <0.01). Conclusions: In ART-experienced children on d4T-containing regimens, we observed lower SFT and higher TC and LDL values compared to ART-naive children and HIV-uninfected controls.